Early T precursor acute lymphoblastic leukaemia/lymphoma shows differential immunophenotypic characteristics including frequent CD33 expression and in vitro response to targeted CD33 therapy. (22nd May 2019) - Khogeer, Haitham; Rahman, Haitham; Jain, Nitin; Angelova, Evgeniya A.; Yang, Hong; Quesada, Andres; Ok, Chi Y.; Sui, Dawen; Wei, Peng; Al Fattani, Areej; Pierce, Sherry; Loghavi, Sanam; et al.
Summary: The differential immunophenotypic characteristics of early T precursor (ETP) acute lymphoblastic leukaemia/lymphoma (ALL) remain incompletely characterized. The study group ( n  = 142) included 106 (74·7%) men and 36 (25·3%) women with a median age of 34·9 years (range, 2–79) at diagnosis. Patients were subtyped by flow cytometry immunophenotyping as follows: 33 (23·2%) ETP; 32 (22·5%) early non‐ETP; 60 (42·2%) thymic ; and 17 (12·1%) mature . Excepting definitional markers, there was a significant differential expression of the markers CD2, CD10, CD33 and TdT between ETP‐ALL and non‐ETP‐ALL. Positive CD33 expression (≥20% of leukaemic blasts) was detected in 21/33 (63%) ETP‐ALL compared with 17/95 (17·9%) non‐ETP‐ALL ( P  < 0·001). Notably, targeted anti‐CD33 therapy with IMGN779 resulted in significant growth inhibition and increased apoptosis in ETP‐ALL cells in vitro . An 11‐marker T‐ALL immunophenotype score discriminated reliably between ETP and non‐ETP ALL. Longitudinal analysis of ETP‐ALL cases in this study demonstrated that the immunophenotype may be occasionally dynamic but is largely stable over the disease course. In summary, identification of ETP‐ALL might be enhanced by using an 11‐marker T‐ALL immunophenotype score. CD33 expression is frequent in ETP‐ALL, and in vitro data suggest that exploring anti‐CD33 therapy in ETP‐ALL is warranted.